Behavioral and Neurophysiological Correlates of Dogs’ Individual Sensitivities to Being Observed by Their Owners While Performing a Repetitive Fetching Task - Kiss, Orsolya; Kis, Anna; Scheiling, Katalin; Topál, József (Frontiers in Psychology, 2020)
Ample evidence suggests that dogs possess enhanced skills in reading human visual attention, but it remains to be explored whether they are sensitive to audience effect in their interactions with humans. The present study aimed to investigate how dogs’ behavior is affected by their owners’ visual attention while performing a repetitive, relatively monotonous task (bringing an object back to an unfamiliar experimenter). We assumed that if dogs are susceptible to the audience effect their task persistence and task performance would vary according to their owners’ attentiveness. A group of adult pet dogs (N=27) were repeatedly presented with an object retrieval task (N=20 trials) while owners either ignored their dogs (Inattentive Owner condition) or paid attention to their dogs’ actions (Attentive Owner condition). Behavioral observations were complemented with information about owner-dog relationship insecurity (assessed by means of an owner-reported questionnaire) and dogs’ spectral EEG sleep profile (recorded during 3-hour-long daytime sleep). Although dogs, independently of their owners’ attentional state, were generally willing to comply with the fetching task, they were faster to approach the toy object and gazed significantly longer at their owners when he/she was paying attention. This finding is reminiscent of peer influence observed in humans. Further, characteristics of relationship insecurity (relationship anxiety and avoidance) was associated with dogs’ task persistence and performance. Dogs of owners with higher relationship anxiety tended to approach the toy object less frequently, and dogs of owners with higher relationship avoidance and anxiety were more hesitant to approach the toy object. We also found that dogs’ individual susceptibility to the audience effect is a trait-like characteristic reflected in the EEG spectral power of both REM and Non-REM sleep as well as in pre-sleep (drowsiness). These results, in line with previous findings, support the notion that dogs have a somewhat human-like susceptibility to the audience effect, a trait which might be linked to more complex mechanisms, such as self-presentation or reputation management, helping the two species to become effective social partners.